The Influence of Celebrity Endorsers on Customer Buying Behavior: Exploring the Impact of Celebrity Endorsers on Consumer Purchasing Decisions (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Despite the rise of numerous promotional methods in recent years, advertising remains themost popular way to promote a product. Celebrity endorsement facilitates the sales of the product orservice in a competitive industry. It is also important for brand recall because the consumer can easilyrecall the goods that is connected with their favourite person. The celebrity endorsers will explain how touse the product as well as the benefits it offers, as well as why customers should buy it. Celebrities aresaid to appear in nearly 20 of all Television commercials, and advertisers pay celebrities hundreds ofmillions for their facilities.